Nocturnal foraging by great skuas Stercorarius skua : implications for conservation of storm-petrel populations - Votier, S.C.; Crane, J.E.; Bearhop, S.; de León, A.; McSorley, C.A.; Minguez, E.; Mitchell, I.P.; Parsons, M.; Phillips, R.A.; Furness, R.W. (Journal of Ornithology, 2006)
At St Kilda, Outer Hebrides, a large colony of great skuas Stercorarius skua feed extensively on one of the largest colonies of Leach's storm-petrels Oceanodroma leucorhoa in Europe, but little is known about the dynamics of this predator-prey system. Recently published population estimates of storm-petrels make it possible to estimate the impact of skua predation for the first time. Although skuas in the southern hemisphere catch petrels attending breeding colonies at night, it is not known whether congeners in the northern hemisphere also forage during the hours of darkness. We found (using radio-transmitters) that skuas regularly forage at night and (using light intensifying equipment) observed them catching storm-petrels at night. However, skuas also foraged during daylight hours, and it is unknown whether they might also catch storm-petrels at sea. Data on diet composition reveals that the proportion of storm-petrels in skua diet declined between 1996 and 1997, but remained constant thereafter. Although a large proportion of the storm-petrel prey is likely to consist of non-breeders, numbers consumed suggest that breeders and an unknown quantity of transients may also been eaten. The numbers of storm-petrels eaten are not sustainable and may result in substantial long-term population declines. Under current conditions, maintenance of large populations of both Leach's storm-petrels and great skuas at St Kilda appears to be mutually exclusive